Correction: Targeting a highly repetitive genomic sequence for sensitive and specific molecular detection of the filarial parasite Mansonella perstans from human blood and mosquitoes. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0010615.].